'Greening the CAP' – Just a fashionable justification? A discourse analysis of the 2014–2020 CAP reform documents. (February 2015) - Erjavec, Karmen; Erjavec, Emil
Highlights: Key discourses of the CAP were transformed in a way that emphasised the environment. The productivist discourse was also strengthened at the level of budget distribution. The study has shown the usefulness of critical discourse analysis for policy analysis. Abstract: Existing studies have employed discourse analysis to examine the reform of the EU's Common Agricultural Policy (CAP) but have only partially studied the implementation of the discourse in the context of CAP measures and budgetary distribution. The present study tries to fill this gap. By conducting a discourse analysis of the latest CAP reform (2014–2020) documents, we attempted to determine which discourses and discourse strategies predominated in the reform's documentation and how they were implemented into measures and budgetary distributions. The findings show that in the process of CAP reform decision-making, European institutions justified the CAP with a transformation of key discourses (productivist, multi-functional and neo-liberal) by emphasising the hugely popular environmental element while, at the same time, employing a strong productivist discourse at the level of measures and the budgetary distribution between the EU member states and farmers' groups. In order to retain a strong CAP as well as the current distribution of financial resources, the European Commission, the European Parliament and the European Council employed greening as a justification strategy as well as a productivist discourse as a major component in determining CAP measures.